Brain Delivery of a Potent Opioid Receptor Agonist, Biphalin during Ischemic Stroke: Role of Organic Anion Transporting Polypeptide (OATP) - Thamer H Albekairi; Bhuvaneshwar Vaidya; Ronak Patel; Saeideh Nozohouri; Heidi Villalba; Yong Zhang; Yeon Sun Lee; Abraham Al-Ahmad; Thomas J Abbruscato (MDPI AG, 2019)
Transporters (expressed) at the blood-brain barrier (BBB) can play an essential role in the treatment of brain injury by transporting neuroprotective substance to the central nervous system. The goal of this study was to understand the role of organic anion transporting polypeptide (OATP1; OATP1A2 in humans and oatp1a4 in rodents) in the transport of a potent opioid receptor agonist, biphalin, across the BBB during ischemic stroke. Brain microvascular endothelial cells (BMECs) that were differentiated from human induced pluripotent stem cells (iPSCs) were used in the present study. The effect of oxygen-glucose deprivation (OGD) and reperfusion on the OATP1 expression, uptake, and transport of biphalin was measured in induced pluripotent stem cells differentiated brain microvascular endothelial cells (iPSC−BMECs) in the presence and absence of an OATP1 substrate, estrone-3-sulfate (E3S). Biphalin brain permeability was quantified while using a highly sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. It was found that iPSC-BMECs expressed OATP1. In vitro studies showed that biphalin BBB uptake and transport decreased in the presence of an OATP1 specific substrate. It was also observed that OGD and reperfusion modulate the expression and function of OATP1 in BMECs. This study strongly demonstrates that OATP1 contributes to the transport of biphalin across the BBB and increased expression of OATP1 during OGD-reperfusion could provide a novel target for improving ischemic brain drug delivery of biphalin or other potential neurotherapeutics that have affinity to this BBB transporter.